Improving metal surface integrity by integrating mechanical stress fields during micron- and nano-abrasive machining - Chen, Zhaojie; Xie, Jin; He, Quanpeng; Yang, Hao; Luo, Yihao (International journal of mechanical sciences, 2023)
•Mechanical stress fields during micro-/nano- machining were integrated for surface integrity.•Flexible nanoscale-bonding and hydrodynamic pressure restrains cutting stress and tool vibration.•It decreases roughness, residual stress and SSD to polished ones in micro-shape diamond grinding.•The machined residual stress related to metal elastic modulus is more greatly improved with larger hardness. The micron-scale fixed-abrasive machining can assure micro-shape accuracy through mechanical cut removal and copying, but the machined surface integrity depends on the nanoscale loose-abrasive machining without mechanical stress concentration. Hence, the mechanical stress fields are synthesized by the hybrid machining of loose-Al2O3-abrasive machining and fixed-diamond-abrasive machining. The objective is to improve the surface integrity in the mechanical machining of difficult-to-cut metals. In order to hold the loose-abrasive in fixed-abrasive mechanical machining, the bonding behaviour and the hydrodynamic pressure were first analysed in relation to flow viscosity and fixed-abrasive-tool rotation, respectively. In the hybrid machining, the surface formation was then modelled in relation to mechanical stress distribution, fixed-abrasive-tool vibration, hydrodynamic pressure, etc. Finally, the surface integrity was investigated in micro-machining of die steel, titanium alloy and Inconel alloy, respectively. It is shown that the nanoscale hydrated particle cluster flexibly bonds the loose-abrasive with the hydrodynamic pressure beyond the critical tool rotation. It can absorb the micron-scale tool vibration to the surface formation, fixed-abrasive wear without ground traces and micro-cut edge burrs. The resulted homogeneous stress also can restrain the uneven residual stress derived from the cut copying of fixed-abrasive machining. The hybrid machining decreases the subsurface damage (SSD), residual compressive stress and surface roughness to the polishing ones in micro-shape grinding, but it is subject to the nanometre-scale size of loose-abrasive, the hydrodynamic pressure and the micron-scale cutting depth of fixed-abrasive. The fixed-abrasive wear rate is higher with larger metal hardness, and the residual stress associated with elastic modulus is more greatly improved. As a result, die steel shows better machinability with a low fixed-abrasive wear rate and residual stress compared to titanium alloy and Inconel alloy. [Display omitted]